2019
DOI: 10.3390/foods8020067
|View full text |Cite
|
Sign up to set email alerts
|

Lysozyme Aptamer-Functionalized Magnetic Nanoparticles for the Purification of Lysozyme from Chicken Egg White

Abstract: Lysozyme is in high demand due to its many favorable characteristics such as being naturally occurring, non-toxic, and easy to digest and absorb. Recently, superparamagnetic nanoparticles with strong magnetic responsiveness have attracted significant interest for enzyme purification. The aptamer of the enzyme can be chemically synthesized rapidly at a large scale using simple and low-cost preparation methods. Therefore, Fe3O4 nanoparticles (Fe3O4 NPs) were prepared by chemical co-precipitation and were then fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…However, it was interesting to note that the development of acidity was greater in control as compared to lysozyme treated samples during storage. It is quite often due to the lysozyme antibacterial nature that results in reduction of lactic acid bacteria activity (Luo et al., 2019). Fat percentage did not vary with lysozyme as well as with storage.…”
Section: Resultsmentioning
confidence: 99%
“…However, it was interesting to note that the development of acidity was greater in control as compared to lysozyme treated samples during storage. It is quite often due to the lysozyme antibacterial nature that results in reduction of lactic acid bacteria activity (Luo et al., 2019). Fat percentage did not vary with lysozyme as well as with storage.…”
Section: Resultsmentioning
confidence: 99%
“…Aptamer and nanomagnetic beads have the advantages of simple preparation, easy modification, and good stability. 39 Therefore, the specific recognition of aptamer and the rapid separation as well as enrichment of nanomagnetic beads are integrated to prepare a new type of extraction material, and the pretreatment method for the detection of AFB 1 is demonstrated to have great significance and value.…”
Section: Resultsmentioning
confidence: 99%
“…However, it was observed that the progression of acidity was faster in control sample contrary to lysozyme added cheese samples. It is mainly due to the antibacterial nature of lysozyme that slowed down the activity of lactic acid bacteria (Luo et al, 2019).…”
Section: Physicochemical Analysis Of Cheesementioning
confidence: 99%